Efecto de la temperatura en isotermas de adsorción de kiwicha (amaranthus caudatus) en hojuelas - Rodríguez Avila, Jorge Oswaldo (2015)
In this study the effect of temperature on the adsorption isotherms at 25 °C and 45 °C amaranth flakes. The isotherms were elaborated by the gravimetric method static saturated salt solutions was evaluated. The fit of the experimental models of GAB, BET, Caurie and Henderson data was evaluated. Was estimate the shelf life of Amaranth flakes, using the Heiss and Eichner model. A sample of 1 g of Amaranth flakes was placed on a perforated plate with saturated salt solutions in the range of 4 to 96% relative humidity into 6 glass bells wich were kep at 25 °C y 45 °C for 15 days (equilibrium condition). At this point the moisture content of the Amaranth flakes stored in each container was determined with the Analyzer Lite water activity (AL 1379). The GAB model showed a good fit of experimental data with correlation coefficients greater than 0.9 and %E less than 10%. The reported monolayer values were (0.0701, y 0.0468 g water/g db) higher tan those calculated with the BET model (0.0565 y 0.0358 g water/g db) for the two temperaturas tested. It is concluded that the best model that fits to the amaranth flakes is GAB model and product life was estimated in terms of water permeability and its effect on permeability, having an estimated ranges life 11.5 and 9.9 months at temperatures between 25 °C and 45 °C respectively.